In vitro effects of thiamethoxam on larvae of Africanized honey bee Apis mellifera (Hymenoptera: Apidae) - Tavares, Daiana Antonia [UNESP]; Roat, Thaisa Cristina [UNESP]; Carvalho, Stephan Malfitano; Mathias Silva-Zacarin, Elaine Cristina; Malaspina, Osmar [UNESP] (Elsevier B.V., 2015)
Several investigations have revealed the toxic effects that neonicotinoids can have on Apis mellifera, while few studies have evaluated the impact of these insecticides can have on the larval stage of the honeybee. From the lethal concentration (LC50) of thiamethoxam for the larvae of the Africanized honeybee, we evaluated the sublethal effects of this insecticide on morphology of the brain. After determine the LC50 (14.34 ng/mu L of diet) of thiamethoxam, larvae were exposed to a sublethal concentration of thiamethoxam equivalent to 1.43 ng/mu L by acute and subchronic exposure. Morphological and immunocytochemistry analysis of the brains of the exposed bees, showed condensed cells and early cell death in the optic lobes. Additional dose-related effects were observed on larval development. Our results show that the sublethal concentrations of thiamethoxam tested are toxic to Africanized honeybees larvae and can modulate the development and consequently could affect the maintenance and survival of the colony. These results represent the first assessment of the effects of thiamethoxam in Africanized honeybee larvae and should contribute to studies on honey bee colony decline. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Neonicotinoid; Larval development; LC50; Nervous system; Sublethal effects